172k views
3 votes
6 + 5y - 4y + 10 + 3x - X

2 Answers

4 votes

Answer:

16 + y + 2x

Explanation:


6 + 5y - 4y + 10 + 3x - x


16 + 5y - 4y + 3x - x


5y - 4y = (5 - 4)y = 1y = y


16 + y + 3x - x


= 16 + y + 2x

User Ivan Wang
by
4.4k points
2 votes

Answer:

2 + + 1 6

Explanation:

Add the numbers:

6 + 5y - 4y + 10 + 3x -x =

1 6 + 5 − 4 + 3 −

Combine like terms:

16 + 5y - 4y +3x - x

16+ 1y + 3x -x

Multiply by 1

16 + 1y + 3x - x

16 + y + 3x - x

Combine like terms:

16 + y + 3x - x

16 + y + 2x

Rearrange terms:

16 + y + 2x

2x + y + 16

User Boreas
by
4.9k points